Nutrição e produtividade da nogueira-macadâmia em razão do parcelamento da adubação mineral - Perdoná, Marcos José; Martins, Adriana Novais; Suguino, Eduardo; Blat, Sally Ferreira; Soratto, Rogério Peres [UNESP] (Sociedade Brasileira de Ciência do Solo, 2014)
Nutrient availability during the year can affect the performance of macadamia (Macadamia integrifolia). However, there is no information about this crop responses to split application of fertilizer under Brazilian conditions. The aim of this study was to evaluate the influence of splitting the application of chemical fertilizers on the nutrition, yield, and quality of nuts of the macadamia nut tree. The experiment was conducted over three growing seasons on an Oxisol in Jaboticabal, State of São Paulo, Brazil. A randomized complete block design with five replications was used. The NPK fertilization treatments were T1 - a single application in October; T2 - two applications, in October and December; T3 - three applications in October, December, and February; and T4 - four applications, in October, December, February, and April. Split application of a chemical source of NPK fertilizer resulted in higher N concentration in the leaves than single application, but it did not affect the concentration of other nutrients. The nut yield was increased when NPK application was split into two, three, or four times from October to April, as compared to single application in October. The recovery rate of nut kernels was not affected by splitting the application of NPK fertilizer.

A disponibilidade de nutrientes durante o ano pode influenciar o desempenho da nogueira-macadâmia (Macadamia integrifolia). Contudo, não existem informações sobre a resposta dessa cultura ao parcelamento da adubação nas condições brasileiras. O objetivo deste trabalho foi avaliar a influência do parcelamento da adubação mineral na nutrição, produtividade e qualidade de frutos da nogueira-macadâmia. O experimento foi conduzido, durante três anos agrícolas, num Latossolo Vermelho, em Jaboticabal, SP. O delineamento experimental foi de blocos casualizados, com cinco repetições. O experimento foi constituído por quatro formas de parcelamento da adubação NPK (T1 - uma única aplicação, em outubro; T2 - duas aplicações, em outubro e dezembro; T3 - três aplicações, em outubro, dezembro e fevereiro; e T4 - quatro aplicações, em outubro, dezembro, fevereiro e abril). O parcelamento da adubação NPK proporcionou maiores teores de N nas folhas que a aplicação em dose única, mas não interferiu nos teores dos demais nutrientes. A produtividade da nogueira-macadâmia foi incrementada de forma similar com o parcelamento da adubação NPK em duas, três ou quatro vezes, entre outubro e abril, em comparação à aplicação única em outubro. A taxa de recuperação de amêndoas não foi interferida pelo parcelamento da adubação NPK.
Nutrition and yield of macadamia nut tree as a result of split application of mineral fertilizer
Keywords: Macadamia integrifolia; época de aplicação; nutrição mineral; taxa de recuperação; Macadamia integrifolia; timing of application; mineral nutrition; recovery rate